DIMENSIONS OF SOUL IN THE QURAN: AN ISLAMIC PSYCHOLOGICAL PERSPECTIVE - Warsah, Idi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2020)
Western theories tend to view the essence of humans in a way of a blank state (tabula rasa), wherein their development will be affected by environmental factors as the determinant variable. However, there are a few differences in the portrayal of humans if scrutinized from al-Qur’an. With conducting a library study, the present study sought to scrutinize the essence of humans along with the affiliated dimensions according to the Qur’anic perspective. The current study drew a conclusion that humans are composed of physical (with the overall physical power therein), psychological, and spiritual dimensions. Humans were born with their inborn good trait alongside the naturally inherent elements such as soul and the active as well as responsive supports from environments so that the two elements as such will construct humans’ behavior. Even though environments will not entirely construct humans’ behavior as commonly targeted by education, the inborn potencies cannot develop automatically without being simultaneously promoted by good and conducive environments in addition to effective education. The foregoing is due to the responsive trait of humans.